Creating health: how to attain perfect health and feel ever youthful - "Chopra, Deepak" (London, 1991)
An essential introduction to Deepak Chopra's theory of the healing power of the mind, Creating Health is the definitive guide to his philosophy about the mind/body connection. Blending Eastern and Western medical philosophy, Chopra puts together a clear and easy path to follow for perfect physical and emotional health. With influences from Ayurveda, the 6,000-year-old tradition of medicine from India, Chopra uses Western terminology to explain how we can reassess health and disease and shows how, by focusing on self-awareness, compassion and the mind, we can improve our physical well being. In this book, he also introduces the benefits of meditation and creative visualization.
Keywords: Health